1982
DOI: 10.1002/pssa.2210720107
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Study of Copper Ferrites

Abstract: Tetragonal and cubic CuFe2O4 are prepared and studied by Mössbauer‐effect technique at room temperature and at 4.2 K with and without applied strong magnetic fields. The cation distributions and the hyperfine parameters are determined and compared with magnetization measurements. The results show that tetragonal CuFe2O4 is an inverse spinel of Néel collinear arrangement of spins and that cubic copper ferrite is not completely inverse with a cation distribution dependent on the heat treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 10 publications
5
14
0
3
Order By: Relevance
“…The spinel lattice is thus highly distorted (c/a&1.06) because of a cooperative Jahn-Teller effect arising from the octahedral cupric ions (4,5). Part of the Cu> ions can be frozen in tetrahedral sites when the ferrites are quenched in air from temperatures higher than 400°C (1,3,6,7). The resulting ferrites show a smaller tetragonal distortion since a great proportion of the cupric ions are located on tetrahedral sites.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The spinel lattice is thus highly distorted (c/a&1.06) because of a cooperative Jahn-Teller effect arising from the octahedral cupric ions (4,5). Part of the Cu> ions can be frozen in tetrahedral sites when the ferrites are quenched in air from temperatures higher than 400°C (1,3,6,7). The resulting ferrites show a smaller tetragonal distortion since a great proportion of the cupric ions are located on tetrahedral sites.…”
Section: Introductionmentioning
confidence: 97%
“…Close to thermodynamic equilibrium at room temperature, the copper ferrites may be described by the structural formula Fe> [Fe>Cu>]O\ , in which the octahedral cations are placed inside square brackets (1)(2)(3). The spinel lattice is thus highly distorted (c/a&1.06) because of a cooperative Jahn-Teller effect arising from the octahedral cupric ions (4,5).…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies showed that the cation distribution in a cubic CuFe 2 O 4 can be given as ðCu x Fe 1Àx Þ T d ½Cu 1Àx Fe 1þx O h O 4 ; in which the parentheses and square brackets denote tetrahedral and octahedral sites, respectively, whereas tetragonal CuFe 2 O 4 is completely inverse, i.e., x ¼ 0 [5,6]. The ground state of Cu 2þ ion in the octahedral crystal field is an orbital doublet 2 E g ðt 6 2g e 3 g Þ and so subject to a Jahn-Teller effect which removes the degeneracy of the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…Its lattice parameters are a 0 5.873 # e and c 0 8.555 # e. Its metallic atoms are in an inverse distribution [1,2]; half the atoms of iron are in the A (tetrahedral) sites and the other half plus the copper atoms in the B (octahedral) sites: Fe A CuFe B O 4 . When preparations of this compound are rapidly quenched from above 760 C, they are cubic with the unit a 0 8.383 # e.…”
Section: Introductionmentioning
confidence: 99%